CD43 expression in B cell lymphoma. Issue 11 (November 1992) - Treasure, J; Lane, A; Jones, D B; Wright, D H
Abstract : AIMS: To determine the expression of CD43 in frozen sections in a range of B cell lymphomas. METHODS: The monoclonal antibody WR14, clustered provisionally in the Fourth Leucocyte Typing Workshop as a CD43 reagent, was investigated by epitope blocking studies on formalin fixed reactive lymph node tissue, using the established CD43 antibody MT1, to validate its use as a CD43 reagent. CD43 expression was studied in 131 immunophenotypically defined B cell lymphomas, including lymphocytic lymphoma (Lc, n = 13), centrocytic lymphoma (Cc, n = 14), and a range of follicle centre cell lymphomas (FCC) including centroblastic/centrocytic follicular (CbCcF, n = 48), centroblastic diffuse (CbD, n = 39), centroblastic/centrocytic diffuse (CbCcD, n = 4), centroblastic follicular and diffuse (Cb FD, n = 3) and centroblastic/centrocytic follicular and diffuse (CbCc FD, n = 1). Nine lymphomas of mucosa associated lymphoid tissue (MALT) were also examined. RESULTS: Epitope blocking studies showed that WR14 is a CD43 reagent that binds to an epitope identical with or close to that recognised by MT1. Eleven of 13 (84%) cases of Lc and 11 of 14 (78%) cases of Cc expressed CD43; 87 of 95 (91%) cases of FCC did not. All eight low grade lymphomas of MALT were negative. One high grade lymphoma, transformed from a low grade MALT lymphoma, was positive for CD43. The expression of CD43 by tumours of B cell lineage was associated with the expression of CD5 (p < 0.001) although either antigen could occasionally be found in the absence of the other. CONCLUSION: CD43 reagents can be used in conjunction with CD5 antibodies for the immunophenotypic discrimination of follicle centre cell lymphomas from non-follicle centre cell lymphomas.